Korelasi antara Tingkat Distres dengan Early-Onset Dementia pada Narapidana LPP Kelas IIB Manado - Pua, Yohanes A.; Pertiwi, Junita M.; Warouw, Finny (Universitas Sam Ratulangi, 2026)
Abstract: Female inmates in correctional institutions are vulnerable to psychological distress, including depression, anxiety, and stress. High levels of distress are associated with an increased incidence of early-onset dementia (EOD), which refers to dementia occurring before the age of 65. This study aimed to determine the correlation between distress levels and EOD among female inmates. This was an analytical observational study with a cross-sectional design, conducted at the Manado Class IIB Women’s Correctional Institution from August to November 2025. Sampling was carried out using the stratified random sampling technique, with DASS-21 and MoCA-Ina questionnaires as research instruments. The results obtained a total of 59 female inmates participated in this study. Most inmates had normal distress levels, including normal depression (59,3%), anxiety (49,2%), and stress (59,3%). Based on EOD assessment, the majority (62.7%) showed cognitive impairment. The Spearman’s correlation test indicated a significant relationship between distress levels and early-onset dementia (p=0.000). In conclusion, there is a significant correlation between distress levels and early-onset dementia among female inmates at the Manado Class IIB Women’s Correctional Institution. Keywords: distress levels; early-onset dementia Abstrak: Narapidana perempuan di lembaga pemasyarakatan rentan mengalami distres, seperti depresi, kecemasan, maupun stres. Tingginya tingkat distres berdampak pada angka kejadian early-onset dementia (EOD), yang merujuk pada demensia di rentang usia <65 tahun. Penelitian ini bertujuan untuk mengetahui korelasi antara tingkat distres dengan EOD pada narapidana LPP Kelas IIB Manado. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Penelitian ini dilakukan di LPP Kelas IIB Manado selama bulan Agustus-November 2025, dengan teknik pengambilan sampel menggunakan stratified random sampling. Instrumen penelitian menggunakan lembar kuesioner DASS-21 dan MoCA-Ina. Jumlah sampel penelitian ini sebanyak 59 narapidana perempuan. Hasil penelitian menunjukkan bahwa mayoritas narapidana perempuan berada pada tingkat distres normal, dengan sebaran tingkat depresi normal (59,3%), tingkat kecemasan normal (49,2%), dan tingkat stres normal (59,3%). Berdasarkan penilaian EOD, mayoritas narapidana perempuan mengalami gangguan kognitif (62,7%). Hasil uji korelasi Spearman mendapatkan nilai signifikansi p<0,01 (p=0,000) yang menunjukkan terdapat korelasi bermakna antara tingkat distres dengan EOD. Simpulan penelitian ini ialah terdapat korelasi bermakna antara tingkat distres dengan early-onset dementia pada narapidana LPP Kelas IIB Manado. Kata kunci: tingkat distres; early-onset dementia